ON PEDAL CURVES OF NORMAL SURFACES OF BIHARMONIC CURVES IN SL2 (R) - Korpinar, Talat; Turhan, Essin (Univ Nis, 2012)
In this paper we obtain some results on the pedal curves of normal ruled surfaces of biharmonic curves in the <(SL2 (R))over tilde>. Also, we find out their explicit parametric equations. Finally, we illustrate our main result.